Bridge design : concepts and analysis - Reis, António J., 1949-; Pedro, José J. Oliveira, 1968- (John Wiley & Sons, Ltd, 2019)
A comprehensive guide to bridge design Bridge Design - Concepts and Analysis provides a unique approach, combining the fundamentals of concept design and structural analysis of bridges in a single volume. The book discusses design solutions from the authors' practical experience and provides insights into conceptual design with concrete, steel or composite bridge solutions as alternatives. Key features: -Principal design concepts and analysis are dealt with in a unified approach.-Execution methods and evolution of the static scheme during construction are dealt with for steel, concrete and composite bridges.-aesthetics and environmental integration of bridges are considered as an issue for concept design.-Bridge analysis, including modelling and detail design aspects, is discussed for different bridge typologies and structural materials.-Specific design verification aspects are discussed on the basis of present design rules in Eurocodes. The book is an invaluable guide for postgraduate students studying bridge design, bridge designers and structural engineers.